2002
DOI: 10.1212/wnl.59.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Late cognitive and radiographic changes related to radiotherapy

Abstract: There was no evidence of a general cognitive decline or progression of white matter changes after 3 years. Results argue for limited damage from XRT at this frequently used dose and volume in the absence of other clinical risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
110
2
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(122 citation statements)
references
References 38 publications
1
110
2
9
Order By: Relevance
“…In cross-sectional studies, clear-cut cognitive defi cits after focal radiotherapy have rarely been reported, and then only with a short follow-up. 8,[16][17][18][19][20][21][22][23] One study reports selective cognitive defi cits 6 years after treatment with focal radiotherapy, 23 whereas two other studies report few cognitive sequelae 6 years or more after radiotherapy. 8,9 However, in our study, which had a mean follow-up of 12 years, we found signifi cant deterioration in the domain of attentional functioning in patients who received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cross-sectional studies, clear-cut cognitive defi cits after focal radiotherapy have rarely been reported, and then only with a short follow-up. 8,[16][17][18][19][20][21][22][23] One study reports selective cognitive defi cits 6 years after treatment with focal radiotherapy, 23 whereas two other studies report few cognitive sequelae 6 years or more after radiotherapy. 8,9 However, in our study, which had a mean follow-up of 12 years, we found signifi cant deterioration in the domain of attentional functioning in patients who received radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, the progression of cognitive defi cits might become apparent only after several years (ie, >6 years, according to our previous report). 8,9,[16][17][18][19][20][21][22][23] If this is the case, the eff ect of cognitive decline versus early tumour progression should be taken into account when treatment plans are defi ned.…”
Section: Introductionmentioning
confidence: 99%
“…In studying neuroblastoma survivors, we had an opportunity to more explicitly assess any potential impact of TBI on neuropsychological functioning without introducing any additional morbidity bias secondary to prior radiation treatment to the brain. This is important since neuroimaging studies have documented a link between cranial irradiation and changes in white matter, [29][30][31][32] neurocognitive deficits, [33][34][35] and impairments in attention, concentration, memory, and learning. [36][37][38] Moreover, by focusing only on advanced stage neuroblastoma, we were better able to ascertain whether there were any specific interactions between treatment and disease entity that could impact neuropsychological development.…”
Section: Discussionmentioning
confidence: 99%
“…Such cognitive changes can occur both pediatric and adult patients and include progressive deficits in shortterm memory, spatial relations, visual motor processing, quantitative skills, and attention [2]. Neurocognitive dysfunction was reported to stabilize spontaneously or to progress over time [5,6]. In some cases, subcortical dementia might result which often is associated with gait disturbance and incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, subcortical dementia might result which often is associated with gait disturbance and incontinence. Due to lack of effective treatment, most patients with this severe complication die after several months or a few years [6].…”
Section: Introductionmentioning
confidence: 99%